A Salutogenic Perspektive: How Khowledge and Attitudes Foster Sence of Coherence and Empowerment in Diabeties Self Care - Syamsiah, Nita; Utami, Astrid Berlian; Erlena; Nurjanah, Uun (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Diabetes mellitus (DM) remains a growing global health burden with serious consequences for morbidity and mortality. Despite this, adherence to diabetes self-care is still suboptimal, particularly in primary healthcare settings. A salutogenic approach, which emphasizes factors that create health rather than only preventing disease, provides a useful lens to understand how knowledge and attitudes can empower patients by strengthening their Sense of Coherence (SOC). Objective: This study aims to examine how knowledge and attitudes strengthen SOC and health empowerment, which in turn influence self-care behaviors in patients with Type 2 Diabetes Mellitus (T2DM), using a Salutogenic Framework at the Patokbeusi Health Center, Subang Regency. A cross-sectional design was used with 86 respondents selected through purposive sampling. Data were collected using validated questionnaires on knowledge, attitudes (HBM constructs), and self-care (SDSCA). Chi-square and Odds Ratio (OR) were used to assess associations. Results: It is found that 60.5% of respondents had low knowledge, 55.8% had poor attitudes, and 58.1% demonstrated low self-care. Knowledge was significantly associated with self-care (p = 0.000; OR = 8.000), as were attitudes (p = 0.004; OR = 4.128). The lowest adherence occurred in physical activity (40.0%) and diet regulation (45.7%). Knowledge contributed to the comprehensibility and manageability dimensions of SOC, while positive attitudes supported empowerment through improved self-efficacy and meaningful engagement. Conclusion: Knowledge and attitudes are key predictors of self-care through their roles in strengthening SOC and empowerment. These findings emphasize the need for structured salutogenic-based programs that build patient resources and empowerment to improve diabetes self-care at the primary care level.